The L7Ae proteins mediate a widespread and highly functional protein–RNA interaction. (1st April 2019) - Lilley, David M.J.
Abstract : The k-turn is a ubiquitous structural motif in RNA forming a very tight kink in the axis of helical RNA that plays an important role in many aspects of RNA function. L7Ae is a member of a superfamily of proteins that bind k-turns in RNA, stabilizing the tightly kinked conformation. They are extremely widespread and are important in the assembly of RNA–protein complexes central to translation, splicing and site-specific RNA modification. The interaction is exploited in order to regulate the synthesis of L7Ae proteins and is itself subject to regulation in box C/D snoRNP assembly by N6 methylation of a key adenine in the k-turn. Lastly, we can exploit the L7Ae–k-turn interaction in the construction of nanoscale assemblies.